Practical Concerns Associated with Single-Number Ratings in Measuring Sound Transmission Loss Properties of Partition Panels - Naveen GARG; Anil KUMAR; Sagar MAJI (Archives of Acoustics)
The paper presents an extensive review investigating the practical aspects related to the use of single- number ratings used in describing the sound insulation performance of partition wall panels and practical complications encountered in precise measurements in extensive frequency range from 50 Hz to 5 kHz. SWOT analysis of various single number ratings is described. A laboratory investigation on a double wall partition panel combination revealed the significant dependence of STC rating on transmission loss at 125 Hz attributed to 8 dB rule. An investigation conducted on devising alternative spectrums of aircraft noise, traffic noise, vehicular horn noise and elevated metro train noise as an extension to ISO 717-1 Ctr for ascertaining the sound insulation properties of materials exclusively towards these noise sources revealed that the single-number rating Rw + Ctr calculated using ISO 717-1 Ctr gives the minimum sound insulation, when compared with Rw + Cx calculated using the alternative spectrums of aircraft noise, traffic noise, etc., which means that material provides a higher sound insulation to the other noise sources. It is also observed that spectrum adaptation term Cx calculated using the spectrum of noise sources having high sound pressure levels in lower frequencies decreases as compared to ISO 717-1 Ctr owing to significant dependence of Ctr at lower frequencies.